Exploring leadership developmental process within executive coaching conversation in Malaysia - Nawab Zadah Khan, Nasreen Khanum; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Omar, Zoharah (Human Resource Management Academic Research Society, 2019)
The demanding and continuous change of today’s business environment drives the demand and pressure for a more effective leadership development in every organization, especially in private organizations. In relation to this, coaching has emerged in the human resource development practice as a powerful development tool in improving leadership skills of executive leaders to drive an organization towards success and better performance. The aim of this research is to conceptualize the learning process within coaching conversation to understand how the process is able to enhance leadership qualities within a leader. This knowledge could facilitate coaches to improve their coaching practice and making impactful changes in coaches’ life. Using a qualitative case study approach, data were collected through semi-structured in-depth interviews that involved nine informants from both coaches and coaches. Selection criteria for the coaches were individuals who have conducted executive coaching programmes extensively as part of their service for more than five years, and have reached to the highest level of professionalism as Professional Certified Coach (PCC). The coaches were selected from individuals who hold executive position in their organizations that has participated in any executive coaching programmes in Malaysia. Currently, as a newly emerged tool, the practice of coaching is evolving faster than the theoretical knowledge supporting it. As such, this study is hoped to bridge the gap, integrate and enhance knowledge on various practices and theories, as well as to deepen the understanding on the learning in the coaching process and maximise its effectiveness.